Black visions of the Holy Land African American Christian engagement with Israel and Palestine - Baumann, Roger 1975- (Columbia series on religion and politics, 2024)
"[This book] explores how expressions of American Black religious politics diverge in their interpretations of the Bible, their public theologies, and their modes of political engagement while simultaneously making universal claims about "the Black Church" and African American collective identity. The book examines these tensions through a study of global solidarities linking African American Christians with Israel and Palestine. Drawing on fieldwork conducted in the United States and in Israel-Palestine, the book analyzes a wide range of responses to the conflict-from pro-Israel African American Christian Zionists who work closely with the religious right to Christian Palestinian solidarity activists who emphasize a common emancipatory project between African Americans and Palestinians. Roger Baumann argues that Black religious politics is best understood in social theoretic terms as a field of contestation--a focus on both political practice and political theory--accounting for competing claims to what "the Black Church" is and what it ought to be doing. He also argues that African American Christian engagement with Israel and Palestine is, in part, an expression of existing identities-based on notions of shared Black church history and culture. Thus, the book demonstrates how this issue provides a new context for reworking the alignment of such existing racial, religious, and political identities in global terms. In analyzing the overlapping significance of race and religion in transnational political engagement with the Israeli-Palestinian conflict, the book also speaks to intensifying debates in American politics about racial polarization and the waning of longstanding bipartisan consensus about the pillars of U.S.-Israel relations.""--